Pengembangan Media Pembelajaran Berbasis Game Edukasi Tema 4 Tentang Bangun Ruang Di Kelas 2 SD: PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS GAME EDUKASI TEMA 4 TENTANG BANGUN RUANG DI KELAS 2 SD - Bella, Bella Fitria Sari; Melly Novalia; Edi Ismanto (Universitas Muhammadiyah Riau, 2024)
Learning media at SD Negeri 164 Pekanbaru City refers to blackboards and books that are already available, but do not yet have effective learning strategies. Lack of student interest in learning in the teaching and learning process which is not in accordance with the current development and needs of students. With increasingly advanced and rapid technological developments, humans can create various tools to carry out activities that support productivity. Like making educational game learning media. This research aims to produce a learning media product for the snakes and ladders educational game theme 4 about building space and to determine the feasibility test, practicality and effectiveness of the educational game snakes and ladders theme 4 about building spaces in class 2 of SD Negeri 164 Pekanbaru City. The research method used is the Research and Development (R&D) research method with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. In the feasibility test, an assessment is carried out by two experts, namely a media expert and a material expert to determine the suitability of the product. Where the results of the feasibility test for media experts got a result of 82% in the